2019
DOI: 10.1002/btpr.2936
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the mechanism of copurification of “difficult to remove” host cell proteins in rituximab biosimilar products

Abstract: Host cell proteins (HCPs) are considered a critical quality attribute and are linked to safety and efficacy of biotherapeutic products. Researchers have identified 10 HCPs in Chinese hamster ovary (CHO) that exhibit common characteristics of product association, coelution, and age‐dependent expression and therefore are “difficult to remove” during downstream purification. These include cathepsin D, clusterin, galectin‐3‐binding protein, G‐protein coupled receptor 56, lipoprotein lipase, metalloproteinase inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Nonspecific binding of PLBL2 to protein A/G beads, at high concentrations could also contribute to the observed differences obtained from using the two methods; however, since those differences were not observed in mAb-1′ samples, it is more likely that PLBL2 has interaction with mAb-4 as previously reported . HCP–mAb interactions have also been identified and investigated by several research groups. , However, direct digestion without the HCP enrichment step would provide a full coverage of all HCPs presented. To fully understand the HCP–mAb interaction and the difference between the direct digestion and affinity depletion workflow, continuous study is ongoing to compare the protein profile and quantification of the HCPs enriched by the depletion step to those bound to mAb by both MRM and proteomics-based approaches.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Nonspecific binding of PLBL2 to protein A/G beads, at high concentrations could also contribute to the observed differences obtained from using the two methods; however, since those differences were not observed in mAb-1′ samples, it is more likely that PLBL2 has interaction with mAb-4 as previously reported . HCP–mAb interactions have also been identified and investigated by several research groups. , However, direct digestion without the HCP enrichment step would provide a full coverage of all HCPs presented. To fully understand the HCP–mAb interaction and the difference between the direct digestion and affinity depletion workflow, continuous study is ongoing to compare the protein profile and quantification of the HCPs enriched by the depletion step to those bound to mAb by both MRM and proteomics-based approaches.…”
Section: Resultsmentioning
confidence: 93%
“…35 HCP−mAb interactions have also been identified and investigated by several research groups. 42,43 However, direct digestion without the HCP enrichment step would provide a full coverage of all HCPs presented. To fully understand the HCP−mAb interaction and the difference between the direct digestion and affinity depletion workflow, continuous study is ongoing to compare the protein profile and quantification of the HCPs enriched by the depletion step to those bound to mAb by both MRM and proteomics-based approaches.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Yet, there are individual differences in characteristics and severity to quality problems among the generated HCPs. These differences can cause additional difficulties in the separation process . For example, the closer the HCP structure to the desired mAb product, the more difficult the separation can become.…”
Section: Discussionmentioning
confidence: 99%
“…Downstream processing often includes protein A affinity purification followed by additional polishing steps to further remove aggregates, charge variants, HCPs, T A B L E 1 A comprehensive list of frequently seen HCPs found throughout different processing steps and host cell DNA (Shukla & Thommes, 2010). A literature search performed on the HCPs present after protein A chromatography revealed that many of the same HCPs are found across the biopharmaceutical industry Singh et al (2020). The HCPs identified were similar despite differences in CHO cell lines, upstream processes or downstream processes (Yuk et al, 2015).…”
Section: Frequently Seen Hcps In Downstream Processing the Mechanisms...mentioning
confidence: 99%